2020
DOI: 10.1186/s40635-020-00312-4
|View full text |Cite
|
Sign up to set email alerts
|

The surviving sepsis campaign: basic/translational science research priorities

Abstract: Objectives Expound upon priorities for basic/translational science identified in a recent paper by a group of experts assigned by the Society of Critical Care Medicine and the European Society of Intensive Care Medicine. Data sources Original paper, search of the literature. Study selection This study is selected by several members of the original task force with specific expertise in basic/translational science. Data extraction and data synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 230 publications
(296 reference statements)
0
18
0
Order By: Relevance
“…The metabolic response to sepsis has long been studied and is still of great interest for guiding therapeutic management of critical illness and long-term morbidity 1 . However, many previously investigated pathways have not led to practice-changing clinical trials, and thus the field is at a stage where many of the well-studied metabolic pathways including glucose production [28][29][30][31] , lactate production 32,33 , and muscle proteolysis 34,35 require greater insight and may require pivoting to the exploration of new metabolic pathways, to translate to standard-of-care precision medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic response to sepsis has long been studied and is still of great interest for guiding therapeutic management of critical illness and long-term morbidity 1 . However, many previously investigated pathways have not led to practice-changing clinical trials, and thus the field is at a stage where many of the well-studied metabolic pathways including glucose production [28][29][30][31] , lactate production 32,33 , and muscle proteolysis 34,35 require greater insight and may require pivoting to the exploration of new metabolic pathways, to translate to standard-of-care precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“… Summary Reprogramming metabolism is of great therapeutic interest for reducing morbidity and mortality during sepsis-induced critical illness 1 . Disappointing results from randomized controlled trials targeting glutamine and antioxidant metabolism in patients with sepsis have begged for both identification of new metabolic targets, and a deeper understanding of the metabolic fate of glutamine at the systemic and tissue-specific manner 24 .…”
mentioning
confidence: 99%
“…An initial 88 questions were reduced to 22 final clinical questions. Subcommittees were tasked with elaborating on their initial contributions, and are previously published [3,4]. Another document specifically addresses research priorities for Coronavirus Disease 2019 [5].…”
Section: Methodsmentioning
confidence: 99%
“…Advances in metabolomics enable profiling of a much greater proportion of human plasma metabolites at decreasing cost. Recently, the task force for the Research Committee of the Surviving Sepsis Campaign identified five key basic and translational science research priorities (16). The first two priorities include: 1) elucidating mechanisms that underlie sepsis and 2) how sepsis alters metabolism.…”
mentioning
confidence: 99%